Dramatic neurological and biological effects by botulinum neurotoxin type A on SH-SY5Y neuroblastoma cells, beyond the blockade of neurotransmitter release - Lei Wang; Carol S. Ringelberg; Bal R. Singh (BMC, 2020)
Abstract Background Gene expression profile analysis on mammalian cell lines and animal models after exposure to botulinum neurotoxin (BoNT) has been investigated in several studies in recent years. Microarray analysis provides a powerful tool for identifying critical signaling pathways involved in the biological and inflammatory responses to BoNT and helps determine the mechanism of the function of botulinum toxins. One of the pivotal clinical characteristics of BoNT is its prolonged on-site effects. The role of BoNT on the blockage of neurotransmitter acetylcholine release in the neuromuscular junction has been well established. However, the effects of the treatment time of BoNT on the human cellular model and its potential mechanism remain to be defined. Methods This study aimed to use gene microarray technology to compare the two physiological critical time points of BoNT type A (BoNT/A) treatment of human neuroblastoma cells and to advance our understanding of the profound biological influences that toxin molecules play in the neuronal cellular system. SH-SY5Y neuroblastoma cells were treated with BoNT/A for 4 and 48 h, which represent the time needed for the entrance of toxin into the cells and the time necessary for the initial appearance of the on-site effects after BoNT application, respectively. Results A comparison of the two time points identified 122 functional groups that are significantly changed. The top five groups are alternative splicing, phosphoprotein, nucleus, cytoplasm, and acetylation. Furthermore, after 48 h, there were 744 genes significantly up-regulated, and 624 genes significantly down-regulated (p‹ 0.01). These genes fell into the following neurological and biological annotation groups: Nervous system development, proteinaceous extracellular matrix, signaling pathways regulating pluripotency of stem cells, cellular function and signal transduction, and apoptosis. We have also noticed that the up-regulated groups contained neuronal cell development, nervous system development, and metabolic processes. In contrast, the down-regulated groups contained many chromosomes and cell cycle categories. Conclusions The effects of BoNT/A on neuronal cells extend beyond blocking the neurotransmitter release, and that BoNT/A is a multifunctional molecule that can evoke profound cellular responses which warrant a more in-depth understanding of the mechanism of the toxin's effects after administration.